Tax-Competition with Involuntary Unemployment - Thomas Eichner; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the present paper we extend the classical tax-competition framework of Zodrow and Mieszkowski (1986) by modelling involuntary unemployment and by allowing for labour taxation as a second source of public funds. For a large class of production functions (including CES), it turns out that tax competition is characterized by underprovision of public goods, and by positive taxes on both labour and capital. We thus conclude that the results of Zodrow and Mieszkowski survive some important and substantial modifications of the framework, and are thus more general than recently suggested elsewhere.
Keywords: H21; H71; H72; J51; 330; tax competition; capital and labour taxation; involuntary unemployment; efficient bargains; Steuerwettbewerb; Kapitalertragsteuer; Lohnsteuer; Steuerwirkung; Unfreiwillige Arbeitslosigkeit; Öffentliches Gut; Versorgung; Theorie